Biological Fixation of a Porous-Coated, Metal-Backed Acetabular Component in Canine Total Hip Arthroplasty - Cockshutt, J. R.; Schatzker, J.; Sumner-Smith, G.; Fornasier, V. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
A total hip surface replacement was successfully performed on eight adult dogs, using a porous-coated, cobalt-chromium- molybdenum alloy acetabular resurfacing component fixed to the acetabulum with 3.5 mm cortical screws. Functional, radiological, histological and fluorochrome labelling studies were used to assess tissue response to the implant. At four months after implantation, seven of the acetabular components were anchored with well organized fibrous tissue. Bone ingrowth had occurred in three components. Failures appeared to be due to technical difficulties encountered during the surgical procedure.
Keywords: Total hip replacement; Biological fixation; Porous-coated acetabular implant